Empirical Analysis of the Relationship between Industrial Performance and Macroeconomic Factors in Ghana - Mensah, Frederick; Ofori-Abebrese, Grace; Pickson, Robert Becker (British Journal of Economics, Management & Trade, 2018)
Article published in the British Journal of Economics, Management & Trade, 2016 found at DOI: 10.9734/BJEMT/2016/25092